Corporate Leadership in the Digital Business Era and Its Impact on Economic Development Across Global Markets - Santoso, Nuke Puji Lestari; Nurmala, Risma; Rahardja, Untung (Pandawan Sejahtera Indonesia, 2025)
The digital business era has transformed corporate leadership, demanding a shift in leadership strategies and organizational structures. With the rapid advancement of digital technologies such as AI, blockchain, and big data analytics, business leaders are challenged to integrate these technologies while fostering innovation and sustainable growth in competitive global markets. This paper explores the relationship between corporate leadership and economic development across various global markets experiencing digital transformation. By examining different leadership styles, digital transformation initiatives, and their economic effects, the study seeks to understand how leadership in the digital era impacts economic outcomes. It highlights the importance of strategic leadership in driving innovation, collaboration, and adaptability, which are crucial for navigating technological disruption. The paper also investigates the regional variations in economic development resulting from digital transformation, offering insights into how different markets respond to digital changes and the leadership approaches that contribute to or hinder growth. In conclusion, this research emphasizes the need for dynamic leadership that is proactive, visionary, and capable of guiding organizations through the complexities of the digital landscape. It suggests that strategic leadership not only drives innovation but also supports global economic growth by helping organizations adapt and thrive in the face of digital disruption.